Turbo-Expander Units on Low Boiling Working Fluids - A. V. Ovsyannik; V. P. Kliuchinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article examines the possibility of increasing the efficiency of the turbo-expander cycles on low-boiling working fluids using those methods that are used for steam turbines, viz. increasing the parameters of the working fluid before the turbo-expander and using secondary overheating. Thus, four schemes of the turbo-expander cycle are considered: the one without overheating of the low-boiling working fluid, the one with single overheating of low-boiling fluid, the one with double overheating and the one with double overheating at supercritical parameters. All the studied cycles were considered with a heat exchanger at the outlet of the turbo expander, designed to heat the condensate of a low-boiling working fluid formed in the condenser of the turbo expander unit. Cycles in P–h coordinates were built for the studied schemes. The method of thermodynamic analysis of the studied cycles based on the exergetic efficiency has been developed. The results of the research are presented in the form of Grassman-Shargut diagrams, which show exergy losses in the elements of the studied cycles on a scale, and also show the positive effect of the operation of the turbo-expander cycle in the form of electrical power. The analysis of the obtained results showed that the main losses that have a significant impact on the exergy efficiency are the losses of exergy in the recovery boiler. The increase of parameters of low-boiling working body, and the use of intermediate superheating reduce losses in the waste heat boiler and, consequently, increases exergetic efficiency of turbo-expander cycle. The turbo-expander cycle with double overheating at supercritical parameters of the low-boiling fluid is of the largest exergetic efficiency out of the schemes that have been examined.